The impact of road improvements on road safety and related characteristics. (March 2017) - Gichaga, Francis John
Abstract: This paper presents the historical and cultural background relating to road improvement and road safety characteristics in Kenya, a developing country in East Africa. Some who come from low-developed areas of developing countries often take time to comprehend the modern transportation infrastructure, especially roads, and have difficulty assimilating and customizing the same to their culturally tailored modes. This paper discusses two case studies: one on the socio-economic impact following improvements to a 50-km, high-class, high-traffic-volume road and the other on the monitoring and evaluation of road safety aspects along the Northern Corridor in Kenya also following major road improvements. The road improvements to the Nairobi-Thika Highway (a trunk road) have attracted many investors along the highway corridor. The high-speed road has also brought with it the unfortunate consequence of speeding vehicles colliding with pedestrians crossing the road at undesignated locations. The Northern Corridor, the transportation corridor that links the Great Lakes Countries of the Democratic Republic of Congo, Burundi, Rwanda, and Uganda from the port of Mombasa in Kenya, has had high accident rates for a considerable amount of time. The results of monitoring and evaluation exercises on the Northern Corridor have shown that drivers are the major contributors in causing accidents, with a component ratio of 49.4%; pedestrians are next at 21.7%. Data also shows that 24% of the accidents along the Northern Corridor are fatal, which is of major concern. The study additionally indicated that the majority of road users have not been exposed to education or training on road safety. This paper presents a number of recommendations arising from the road safety study regarding possible improvements in aspects of road safety along the corridor and potential applications of those changes to other roads in general. For example, there are recommendations related to the geometric design of the road, driver training and behavior, vehicle maintenance, and the need to enhance road safety through the utilization of road safety parks where road users can undergo training and drills on road safety aspects. In conclusion, we argue that the rehabilitation of the Northern Corridor from Mombasa on the Kenyan coast to the border with Uganda has led to significant road safety improvement.